2010
DOI: 10.1002/rra.1440
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of abiotic and biotic gradients downstream a multiple use reservoir in a Mediterranean River

Abstract: The effect of regulated flow regimentation on hydrogeomorphological variables, autochthonous and allochthonous trophic sources and macroinvertebrates communities of the Mucone River, Calabria (Italy) were studied in May, August and November 2005 at three study sites.The first site (M1) was located close to the impoundment, the second one (M2) immediately upstream from the first permanent tributary (Cerreto stream) and the third one (M3) about 1 km downstream from the Cerreto confluence.Our results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This stresses worse negative influence of impoundments (UD sites) due to lower water velocity and consequent accumulation of finer sediment as reported by Eggert et al [10]. The negative effects of accumulation of finer sediments on lotic communities have been reported by Wood and Armitage [45], Larsen et al [46] and Lucadamo et al [47] and include low stability [10], reduction of available space and oxygenation of substrate [48]. Chester and Norris [49] reported that the macroinvertebrate community changed from an EPT-dominated community to one dominated by Oligochaeta and Chironomidae.…”
Section: General Observationsmentioning
confidence: 59%
See 1 more Smart Citation
“…This stresses worse negative influence of impoundments (UD sites) due to lower water velocity and consequent accumulation of finer sediment as reported by Eggert et al [10]. The negative effects of accumulation of finer sediments on lotic communities have been reported by Wood and Armitage [45], Larsen et al [46] and Lucadamo et al [47] and include low stability [10], reduction of available space and oxygenation of substrate [48]. Chester and Norris [49] reported that the macroinvertebrate community changed from an EPT-dominated community to one dominated by Oligochaeta and Chironomidae.…”
Section: General Observationsmentioning
confidence: 59%
“…The distance from the source explains 17% of the variability in the community. Lucadamo et al [47] explain its influence in terms of substantial change of several parameters downstream, including flow velocity [64], substratum [59] and temperature [65]. Conductivity (7%) plays a minor role in shaping the composition of the macroinvertebrate community.…”
Section: Influence Of Environmental Factors On Composition Of the Macmentioning
confidence: 99%
“…Changes in natural flow of rivers result in loss of biological diversity because water flow is one of the main forces structuring freshwater ecosystems (see Junk et al, 1989). The type and extent of the impacts of anthropogenic changes on biotic communities depend mainly on the intended water use (navigation, hydroelectricity generation, irrigation supply, and domestic water supply) (Lucadamo et al, 2012;Humphries et al, 2014). Consequently, freshwater ecosystems are among the most threatened ecosystems and exhibit a high rate of species extinction (Myers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively recent anthropo-genic changes to riverine ecosystems have altered patterns of flow discharge, interfering with the distribution and abundance of organisms of lower trophic levels from which most fish derive their food (e.g. Cortes et al 2002;Lucadamo et al 2012;Jones 2013). Dam discharge can impact the feeding ecology of downstream biota in four distinct ways: (i) causing a physicochemical disturbance associated with the release of water from the hypolimnion, which is frequently nutrient rich (Ward & Stanford 1989); (ii) modifying the available food resources through changes in the downstream transfers of particulate organic matter (Petts 1984); (iii) creating a disruption in the hydrological patterns and pulses of invertebrate drift following water releases (Lauters et al 1996); and (iv) diversion and water abstraction downstream of the dam that may result in flood suppression by drastically decreasing the diversity of animal prey (Agostinho et al 2008).…”
Section: Introductionmentioning
confidence: 99%